Managing Diversity at the Workplace in a Global Economy: Challenges & Opportunities - Nagar, Minakshi (Prabandhan: Indian Journal of Management, 2012)
Diversity is a very sensitive topic and is discussed under such labels as civil rights, affirmative action, reverse discrimination, quotas, racism, and sexism. All human organizations have "differences". People are different not only in gender, culture, race, social and psychological characteristics, but also in their perspectives and prejudices. As the world continues the process of globalization, workplace diversity is becoming a common phenomenon. Managing diversity is an on-going process that unleashes the various talents and capabilities which a diverse population brings to an organization, community or society, so as to create a wholesome, inclusive environment, that is "safe for differences", enables people to "reject rejection", celebrates diversity, and maximizes the full potential of all, in a cultural context where everyone benefits. Some studies suggest that it means approaching diversity at three levels simultaneously: individual, interpersonal, and organizational. The traditional focus has been on interpersonal and individual aspects alone. At its best, it means getting from employees not only everything you have a right to expect, but everything they have to offer (R. Roosevelt Thomas). The Objectives of the paper are: 1) To explain the concept of diversity and the reasons for its emergence. 2) To examine the impact of diversity on the business performance and to analyze the factors influencing the impact of diversity. 3) To highlight the various business strategies for managing diversity in the workplace.